EFFECTS OF ANTHROPOGENIC ACTIVITY ON STREAM WATER QUALITY IN LANGSA, ACEH - Helmy Akbar; Iwan Suyatna; Jailani Jailani; Singgih Afifa Putra; Fauziah Azmi (Universitas Mataram, 2018)
Increased human activity towards the water bodies will change the condition of water quality. Case study in Langsa, Aceh, It was found that an increase in Some physical parameter (TSS) that exceeds the value determined in PP 82 of 2001 (Indonesian government standard). The high value of TSS in Station 2 and Station 3 indicates that the sediment loading to the water body is high, especially in Station 3, where the TSS concentrations far exceed the standard. Activity of type C surface mining materials tends to affect the brightness, turbidity, depth and TSS. Water conditions with low pH were also found in this study. In location studied no EPT larvae were foundÃÂ Keyword: Langsa, Water Quality, Stream, Total Suspended Solid, Anthropogenic Activity